Pengaruh Poster Peduli Lingkungan Terhadap Perilaku Siswa Dalam Menjaga Lingkungan Sekolah - Nurhayati Puja Afrianti; Wildan Adib Furqon; Annisa Wulandari (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2024)
This research aims to examine the influence of poster media on student behavior in maintaining the cleanliness of the school environment at SD N 1 Tlogojati. Posters as visual media are used to increase students' awareness and motivation in maintaining the cleanliness and sustainability of the school environment. The method used is descriptive quantitative with data collection techniques through questionnaires and interviews. The research subjects were 25 grade 5 students at SD N 1 Tlogojati. The research results show that the use of poster media has a positive influence on student behavior. Attractive and informative posters can increase awareness and motivate students to behave pro-environmentally. Students become more aware of the importance of disposing of waste in the right place, separating organic and non-organic waste, and participating in environmental activities such as community service and recycling programs. Apart from that, posters also help teachers convey material more effectively and attract students' attention. In conclusion, poster media can be an effective tool in supporting environmental education programs in schools and increasing student awareness and participation in maintaining a clean environment.